Factors Associated with 30-Day Hospital Readmission Among Nursing Home Residents - Kojima, Gotaro (University Clinical, Education & Research Associate (UCERA), 2013)
BACKGROUND: Hospital readmissions within 30 days are increasingly targeted as a quality parameter. Frail nursing home patients are at high risk for hospitalization. The purpose of this study was to examine baseline prevalent chronic diseases associated with hospital readmission within 30 days. METHODS: We collected data on demographics and prevalent diseases for all patients admitted to one hospital-affiliated nursing home between January 2003 and December 2006, with follow-up data on pneumonia episodes and hospitalizations through June 2011. Multivariable logistic regression models identified baseline prevalent chronic diseases associated with hospital readmission within 30 days of nursing home admission. RESULTS: Of 238 patients (mean age 83.4, range 45-103) admitted to the nursing home, 156 (65.5%) originally came from hospitals, 54.6% were female, 92.4% were Asian, 43.6% were on Medicaid, and 76.5% were first admitted for intermediate care and 23.5% for skilled nursing care. Although recent pneumonia was the factor most strongly associated with hospital readmission (OR = 14.5, P <.0001), in the model without pneumonia, chronic diseases associated with 30-day hospital readmission included pulmonary disease (OR = 2.2, 95%CI = 1.1–4.3, P = .019) and congestive heart failure (OR = 1.8, 95%CI = 1.0–3.4, P = .055). There were no significant associations between hospital readmission and myocardial infarction, stroke, cancer, diabetes, and dementia. CONCLUSIONS: Among nursing home patients, although recent pneumonia was the strongest risk factor for 30-day hospital readmission, those with baseline chronic pulmonary disease and congestive heart failure were at especially high risk for hospital readmission within 30 days of nursing home admission. These patients may benefit from care focused on preventing hospital readmissions.